Plant Breeding Current and Future Views - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2021)
Plant Breeding - Current and Future Views provides scientific views from leading international scientists on the latest advances in plant breeding, in particular new crop development, breeding for stressful conditions, new tools in plant molecular breeding, and crop biotechnology. The chapters present new updates in the field of plant breeding, covering the scientific efforts and solutions of the world's plant science research community in the era of technological advance and global climate change.